Design and implementation of a real-time hardware-in-the-loop testing platform for a dual-rotor tail-sitter unmanned aerial vehicle. (December 2018) - Sun, Jingxuan; Li, Boyang; Wen, Chih-Yung; Chen, Chih-Keng
Abstract: Tail-sitter vertical take-off and landing (VTOL) vehicle is a promising airframe among all the unmanned aerial vehicles (UAV), although challenges regarding the control strategies remain for civil applications, such as high susceptibility to wind disturbance while hovering. A real-time hardware-in-the-loop (HIL) simulation method for a tail-sitter UAV, an efficient tool for developing the control system, is presented in this paper. A nonlinear six-degrees-of-freedom dynamic model that covers the full angle-of-attack range is derived using the component breakdown approach. The environmental model is further introduced in the real-time simulation application to provide prevailing and gust wind conditions. A commonly used open-source flight controller was embedded in the proposed HIL framework. This HIL testbed can help researchers minimise the time spent debugging the controller program and moving from the simulation control system to the practical control one. The HIL simulation system was validated with the typical complete flight scenarios of a tail-sitter, including hovering, forward transition, cruise, and back transition. The results demonstrate that the HIL system can be an efficient tool for verifying the performance of hardware and software designs of the control system at the development stage for tail-sitter UAVs.